Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1136/jech-2014-204960
|View full text |Cite
|
Sign up to set email alerts
|

Health service use, out-of-pocket payments and catastrophic health expenditure among older people in India: The WHO Study on global AGEing and adult health (SAGE)

Abstract: Reducing out-of-pocket health expenditure among older people is an important public health issue, in which social as well as medical determinants should be prioritised. Enhanced public health sector performance and provision of publicly funded insurance may protect against catastrophic health expenses and healthcare inequities in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 36 publications
12
91
2
3
Order By: Relevance
“…More than two thirds of total health expenditures are paid directly by the service users and their families as OOPHE in many LMICs (19). When these OOPHE exceed a household's ability to pay, they turn into catastrophic health expenditures (CHE), and can lead to indebtedness, poverty, and hunger (20).…”
Section: Health Economic Challenges For Older People In Lmicsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than two thirds of total health expenditures are paid directly by the service users and their families as OOPHE in many LMICs (19). When these OOPHE exceed a household's ability to pay, they turn into catastrophic health expenditures (CHE), and can lead to indebtedness, poverty, and hunger (20).…”
Section: Health Economic Challenges For Older People In Lmicsmentioning
confidence: 99%
“…When they could no longer work, they lost their source of income, and they did not get pension support or medical benefits from their past employers or Governments. Such older people were financially dependent on their families, and their families were burdened by increasing care needs and increasing OOPHE (19).…”
Section: Health Economic Challenges For Older People In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Out-of-pocket health expenditures were higher among participants with increased the number of health visits as shown in a study on health service use by Brinda EM, Kowal P, Attermann J, Enemark U. 7 Catastrophic health expenditure and rural household impoverishment study done in China concluded that higher percentage of households experiencing catastrophic health expenditure and medical impoverishment correlates to increased health care need. 8 This study was limited in Information on social security schemes availed by families which would have given exact insight into out of pocket expenditure on health.…”
Section: Resultsmentioning
confidence: 98%
“…Older men and individuals with chronic diseases were at higher risk of catastrophic health expenditure. 23 In India CHE was experienced by 84 per cent as a consequence of treating acute coronary syndromes (ACS). 17 For ACS, Catastrophic health expenditure was reported by 66% of those without insurance versus 52% of those with health insurance.…”
Section: Introductionmentioning
confidence: 99%